The factors that affect the retirement saving plan / Nurul Amira A. Rahman - A.Rahman, Nurul Amira (2013)
Awareness in retirement is still a vague issue among societies in Malaysia. Despite a growing awareness for the need to prepare for one's retirement, many do not translate their plans into action. Usually they have a fairly good understanding of the basic mechanics of the plan but they have insufficient knowledge to differentiate among numerous investment options. The reality hits when people find that they cannot afford to retire because they have not seriously put aside the money in their early life. Abdul Samad and Kari, (2007) conducted a survey on 2,000 retirees in Malaysia. The results revealed that the benefits provided by the Employees Provident Fund were not adequate to sustain their retirement life. Therefore, this paper, subjectively, aims to investigate the factors that affecting the retirement saving plan. This thesis utilizes questionnaire-based surveys to collect the information and the data are analyzed using Statistical Package for the Social Sciences (SPSS) software .The findings of this research indicate the perceived importance of age, financial advisor and financial investment knowledge as the significant predictors for individuals to invest part of their retirement savings in the unit trusts. According to Choong (2005), the Malaysian unit trust industry has been one of the fastest-growing sectors within the finance industry in the last two decades. In conclusion the working individuals should do early planning for retirement to enable them to have a strong financial base after retirement.